Effects of Institutionalization and Parental Living Status on Children’s Self-Esteem, and Externalizing and Internalizing Problems in Rwanda - Nsabimana, Epaphrodite; Rutembesa, Eugène; Wilhelm, Peter; Martin-Soelch, Chantal (Frontiers in Psychiatry, 2019)
The negative effects of institutionalization on children’s wellbeing and psychological adjustment have been extensively documented. Throughout the world, particularly in developing countries, many children in residential child care institutions known as orphanages have parents, and it is not clear how this situation affects the psychological adjustment of institutionalized children. This study aimed at investigating specifically whether institutionalization impacts negatively children’s psychological adjustment defined in terms of externalizing and internalizing behavior problems and self-esteem and whether having living parents or not has an additional influence. Children were recruited in Rwanda from seven registered institutions and six primary schools. Ninety-six institutionalized children (48 orphans, who lost at least one parent, and 46 non-orphans, who had both parents living) and 84 non-institutionalized children, who lived in a family (28 orphans and 56 non-orphans) aged 9 to 16 participated. The caregivers or parents assessed externalizing and internalizing behavior problems using the Child Behavior Checklist. Children completed the Coopersmith Self-Esteem Inventory. Controlling for gender, age, and residential area, analyses of covariance revealed that institutionalized children had significantly more externalizing behavior problems than had non-institutionalized children. In addition, non-orphans had more externalizing behavior problems than had orphans, regardless of whether they lived in an institution or not. There were no group differences in internalizing behavior problems, but there was a significant main effect of the parental living status (orphans vs. non-orphans) and a significant interaction effect between parental living status and institutionalization on self-esteem. Self-esteem of non-orphans in families was significantly higher than self-esteem of the other groups. This should be considered when making the decision to place a child in an institution, especially when her or his parents are still living, and when developing supportive programs for children without adequate parental care.